RENTAL APPLICATION INFORMATION SYSTEM DESIGN IN THE BEYOND MUSIC STUDIO - Ahmad Mursalin; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Beyond Studio is a music studio that can be used for band practice for each of itscustomers. Where every day is always filled by the customer.In ordering the payment system or play clock, customers often complain that they didnot get a receipt of payment and hours are often not fully booked with othercustomers.Through the support software, namely Microsoft Access 97 can be used to make thenext customer data stored in computer data storage, and by using Visual Basicprogram so our customers will automatically get a receipt of payment after eachgame.